Crystallographic and magnetic structure of polycrystalline Zn7-xNixSb2O12 spinels - Lisboa Filho, Paulo Noronha [UNESP]; Gama, L.; Paiva-Santos, C. O.; Varela, José Arana [UNESP]; Ortiz, W. A.; Longo, Elson [UNESP] (Elsevier B.V., 2000)
The crystallographic and magnetic structure of sintered, polycrystalline samples of zinc-antimony spinel, Zn7-xNixSb2O12, have been investigated. The samples were prepared by the modified polymeric precursors method. The magnetic contributions of the Ni2+ ions distributed in three non-equivalent crystallographic sites were investigated, revealing the occurrence of different magnetic regimes. A hysteresis response in the magnetic susceptibility indicates a spin-glasslike behavior at low temperatures. (C) 2000 Elsevier B.V. S.A. All rights reserved.
Keywords: sol-gel processing; magnetic structure; zinc antimoniate